Estudo comparativo da satisfação com o suporte social entre trabalhadores noturnos e não noturnos - Andrade, Raphael Zardini (2016)
Night shift work causes disruption in social life, which allegedly adversely affects the efficiency and satisfaction with social relations that shift workers maintain outside the work environment. The aim of this study was to compare satisfaction with social support between night shift and non night shift workers and study possible associations of this investigation with chronotype and BMI. Method: The study was carried out in a poultry processing agribusiness in the interior of Brazil. Four hundred and twenty three (423) workers, night shift (n=168) and non night shift (n=255) of both sexes were evaluated. The volunteers answered a questionnaire that assessed sociodemographic aspects, working hours, sleep quality, usual hours of sleep and awakening. Weight and height were measured to calculate body mass index (BMI), being also measured the waist circumference. The chronotype was evaluated by means of the identification questionnaire as to morning and evening individuals by Horne and Ostberg. The scale of satisfaction with social support (ESSS) and adapted crossculturally Brazil/Portugal was previously submitted to evaluation of psychometric properties for later use in shift workers. Results: The study of the ESSS psychometric properties for the population of shift workers revealed the need for re-specification of the instrument compared to the initial model of 15 items, leading to the exclusion of four items, with a version of the instrument with 11 items that assess four dimensions being proposed. The night shift workers were perceived to be less satisfied with the overall social support (p = 0.04) and with a degree of intimacy (p = 0.01) in their interpersonal relationships. Younger night shift workers (18-30 years) presented lower scores in satisfaction with the overall social support (p<0.01), satisfaction with friends (p = 0.02), social activities (p = 0.03) and intimacy (p = 0.01). The grouping of all shift workers showed positive associations between chronotype and overall social support (p = 0.01, p = 0.134) and satisfaction with friends (p < 0.01, p = 0.158) and between age and satisfaction with friends (p = 0.04, p = -0.109). Conclusion. Workers on the night shift, especially those aged between 18-30 years, showed lower satisfaction with social support, suggesting that the different social experiences related to age can influence perceptions of support. The morning shift work seems to lead to greater satisfaction with social support, whereas less satisfaction with social support may lead to an increase in BMI.